Bait contracts - Marie-Louise Vierø (Queen's University, Department of Economics, 2009)
The granting of stock options to employees who have negligible impact on company performance intuitively violates Holmstrom's (1979) sufficient statistic result. This paper revisits the sufficient statistic question of when to condition a contract on an outside signal in a principal-agent model in which I introduce imprecise (or vague) information. The paper applies a choice theoretic framework introduced in Olszewski (2007) and Ahn (2008) and extended by Viero (2009a), who denoted it vague environments. I show that if the signal is vague, Holmstrom's result can be overturned.
Keywords: D20; D80; D82; D86; 330; contracts; vagueness; optimism; incentives; signals; stock options; Arbeitskräfte; Aktienoption; Vertragstheorie; Unvollkommene Information; Prinzipal-Agent-Theorie